2022
DOI: 10.3389/fpls.2022.1077710
|View full text |Cite
|
Sign up to set email alerts
|

The root transcriptome dynamics reveals new valuable insights in the salt-resilience mechanism of wild grapevine (Vitis vinifera subsp. sylvestris)

Abstract: IntroductionMost of elite cultivated grapevine varieties (Vitis vinifera L.), conventionally grafted on rootstocks, are becoming more and more affected by climate changes, such as increase of salinity. Therefore, we revisited the valuable genetic resources of wild grapevines (V. sylvestris) to elaborate strategies for a sustainable viticulture.MethodsHere, we compared physiological and biochemical responses of two salt-tolerant species: a wild grapevine genotype “Tebaba” from our previous studies and the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…Notably, when the 24 h of stress was compared against the 2 h of stress (R5–R4), it exhibited the highest number of up- and down-regulated transcripts. Likewise, transcriptomic analysis of salt-tolerant wild grapevine Tebaba roots throughout salinity depicted similar results commensurate with the accumulation of polyphenol content and enhancement of antioxidant enzymatic activities [ 34 ]. The longer the time under salinity (in the range of 24–48 h), the higher the changes at the molecular, metabolic, and physiological levels.…”
Section: Discussionmentioning
confidence: 86%
“…Notably, when the 24 h of stress was compared against the 2 h of stress (R5–R4), it exhibited the highest number of up- and down-regulated transcripts. Likewise, transcriptomic analysis of salt-tolerant wild grapevine Tebaba roots throughout salinity depicted similar results commensurate with the accumulation of polyphenol content and enhancement of antioxidant enzymatic activities [ 34 ]. The longer the time under salinity (in the range of 24–48 h), the higher the changes at the molecular, metabolic, and physiological levels.…”
Section: Discussionmentioning
confidence: 86%
“…Soluble sugar metabolism contributes to salt tolerance [13,14]. Starch and sucrose metabolism is involved in the salt stress response in plants [13,14,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Soluble sugar metabolism contributes to salt tolerance [13,14]. Starch and sucrose metabolism is involved in the salt stress response in plants [13,14,42,43]. For example, Chen et al [43] found that DEGs associated with phenylpropanoid biosynthesis and starch and sucrose metabolism were involved in the salt stress response in maize.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before running MAKER, RNA-seq reads from diverse tissues in grapevine and protein sequences from related species were used to provide initial support for gene models. To do so, RNA-seq samples from previous studies [37][38][39][40][41][42] were downloaded from the NCBI Sequence Read Archive (SRA) using fasterq-dump v2.10.7 from the sra-toolkit [43] (see Supplementary Table S2 for the SRA IDs of the specific files used). Trimmomatic v0.39 [26] was used to trim adapters from Illumina RNAseq reads with the flags: --phred33 and ILLUMINACLIP:TruSeq3-PE-2.fa:2:30:10.…”
Section: Dakapo Genome Annotationmentioning
confidence: 99%